Advertising in computer games as a product promotion at modern market - Skryhun, Natalya; Zorenko, A.; Badeshchenkova, Кaterina (My University, 2012)
It is explored and described the impact of advertising on consumers in computer games. It is determined the basic aspects which are the most important for making advertisements for computer games. It is clarified the main regulations that may encourage players in computer games to purchase separate products. It is established the advantages and disadvantages of advertising in computer games and variations of such means of product promotion from traditional means of advertising.
Keywords: реклама; реклама; advertising; рекламування; комп’ютерні ігри; online-ігри; медіаносій; promoting; computer games; online-games; media; кафедра маркетингу